Intravenous immunoglobulin for maintenance treatment of chronic inflammatory demyelinating polyneuropathy: a multicentre, open-label, 52-week phase III trial. Issue 10 (2nd August 2017) - Kuwabara, Satoshi; Mori, Masahiro; Misawa, Sonoko; Suzuki, Miki; Nishiyama, Kazutoshi; Mutoh, Tatsuro; Doi, Shizuki; Kokubun, Norito; Kamijo, Mikiko; Yoshikawa, Hiroo; Abe, Koji; Nishida, Yoshihiko; et al.
Abstract : Objective: Short-term efficacy of induction therapy with intravenous immunoglobulin (Ig) in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) is well established. However, data of previous studies on maintenance therapy were limited up to 24-week treatment period. We aimed to investigate the efficacy and safety of longer-term intravenous Ig therapy for 52 weeks. Methods: This study was an open-label phase 3 clinical trial conducted in 49 Japanese tertiary centres. 49 patients with CIDP who fulfilled diagnostic criteria were included. After an induction intravenous Ig therapy (0.4 g/kg/day for five consecutive days), maintenance dose intravenous Ig (1.0 g/kg) was given every 3 weeks for up to 52 weeks. The primary outcome measures were the responder rate at week 28 and relapse rate at week 52. The response and relapse were defined with the adjusted Inflammatory Neuropathy Cause and Treatment scale. Results: At week 28, the responder rate was 77.6% (38/49 patients; 95% CI 63% to 88%), and the 38 responders continued the maintenance therapy. At week 52, 4 of the 38 (10.5%) had a relapse (95% CI 3% to 25%). During 52 weeks, 34 (69.4%) of the 49 enrolled patients had a maintained improvement. Adverse events were reported in 94% of the patients; two patients (66-year-old and 76-year-old men with hypertension or diabetes) developed cerebral infarction (lacunar infarct with good recovery), and the other adverse effects were mild and resolved by the end of the study period. Conclusions: Maintenance treatment with 1.0 g/kg intravenous Ig every 3 weeks is an efficacious therapy for patients with CIDP, and approximately 70% of them had a sustained remission for 52 weeks. Thrombotic complications should be carefully monitored, particularly in elderly patients with vascular risk factors. Trial registration number: ClinicalTrials.gov (NCT01824251 ).